Transparent conductive film

A transparent conductive film with a fibrous conductor and protective layer addresses the low transmittance issue of metal oxide films, providing high near-infrared light transmission and low resistance for applications like transparent heaters and LiDAR.

JP2025009782AInactive Publication Date: 2025-01-20NITTO DENKO CORP

Patent Information

Application Number
JP2024035730
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-06-28
Filing Date
2024-03-08
Publication Date
2025-01-20
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Conventional transparent conductive films with metal oxide layers, such as ITO, have low light transmittance in the near-infrared region, making it difficult to achieve desired resistance values while considering light transmittance.

Method used

A transparent conductive film comprising a base material with a conductive layer made of fibrous conductors, such as metal nanowires, and a protective layer, which maintains high light transmittance and low surface resistance, particularly in the near-infrared region.

Benefits of technology

The film achieves excellent translucency in the near-infrared region with a surface resistance of 100Ω/□ or less and light transmittance of 85% or more, suitable for applications like transparent heaters and LiDAR systems in autonomous vehicles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025009782000001_ABST
    Figure 2025009782000001_ABST
Patent Text Reader

Abstract

To provide a transparent conductive film excellent in light transmissivity in a near infrared region.SOLUTION: A transparent conductive film includes a base material and a conductive layer arranged at least on one side of the base material. The transparent conductive film has a surface resistance value of 200 Ω / sq. or less. The transparent conductive film has a light transmissivity rate of 85% or higher in a wavelength region of 780 to 2500 nm.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a transparent conductive film. [Background technology]

[0002] Conventionally, transparent conductive films in which a metal oxide layer such as an indium-tin composite oxide layer (ITO layer) is formed on a resin film have been widely used as transparent conductive films for use in electrodes of touch sensors, etc. However, transparent conductive films with a metal oxide layer formed on them have low light transmittance in the near-infrared region, and when light transmittance is taken into account, there is a problem that it is difficult to obtain a desired resistance value. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Special Publication No. 2009-505358 Summary of the Invention [Problem to be solved by the invention]

[0004] The present invention has been made to solve the above problems, and a main object of the present invention is to provide a transparent conductive film that is excellent in light transmittance in the near infrared region. [Means for solving the problem]

[0005] [1] A transparent conductive film according to an embodiment of the present invention is a transparent conductive film comprising a substrate and a conductive layer disposed on at least one side of the substrate, the transparent conductive film having a surface resistance of 200 Ω / □ or less and a maximum light transmittance of 85% or more in a wavelength range of 780 nm to 2500 nm. [2] The transparent conductive film of [1] above may have a surface resistance of 100 Ω / □ or less. [3] The transparent conductive film of [1] or [2] above may have a ratio (T905 / T555) of the light transmittance at a wavelength of 905 nm (T905) to the light transmittance at a wavelength of 555 nm (T555) greater than 0.95 and less than or equal to 1.1. [4] The transparent conductive film according to any one of the above [1] to [3] may have a maximum light transmittance of 85% or more in a wavelength region of 900 nm to 1600 nm. [5] The transparent conductive film according to any one of the above [1] to [4] may have a light transmittance of 85% or more at a wavelength of 905 nm. [6] In the transparent conductive film according to any one of the above [1] to [5], the conductive layer may contain a fibrous conductive material and a polymer matrix. [7] In the transparent conductive film [6] above, the fiber-based conductive material may be metal nanowires. [8] The transparent conductive film according to any one of the above [1] to [7] may be used for a transparent heater. Effect of the Invention

[0006] According to an embodiment of the present invention, a transparent conductive film having excellent light transmittance in the near infrared region can be provided. [Brief description of the drawings]

[0007] [Figure 1] 1 is a schematic cross-sectional view of a transparent conductive film according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to these embodiments.

[0009] A. Overall structure of transparent conductive film 1 is a schematic cross-sectional view of a transparent conductive film according to one embodiment of the present invention. The transparent conductive film 100 includes a substrate 10 and a conductive layer 20 disposed on at least one side of the substrate 10. In one embodiment, the conductive layer 20 includes a fiber-based conductive material 21. Examples of the fiber-based conductive material include metal nanowires and carbon nanotubes. Metal nanowires are preferably used. Although not shown, the transparent conductive film may further include any other appropriate layers.

[0010] In one embodiment, the transparent conductive film 100 includes a protective layer 30 disposed on the opposite side of the conductive layer 20 from the substrate 10. The protective layer 30 may be a layer that protects the fiber-based conductive material 21. In an embodiment of the present invention, the durability of the conductive layer 20 can be improved by providing the protective layer 30. More specifically, a conductive layer made of a fiber-based conductive material (e.g., metal nanowires) is characterized by low scratch resistance, low moisture resistance, etc., and the provision of a protective layer can solve these problems and improve the durability of the conductive layer (and thus the durability of the transparent conductive film). The conductive layer 20 may contain a component that constitutes the protective layer 30 (e.g., a resin that constitutes the protective layer).

[0011] The surface resistance of the transparent conductive film is 200Ω / □ or less, preferably 0.01Ω / □ to 200Ω / □, more preferably 1Ω / □ to 180Ω / □, particularly preferably 5Ω / □ to 150Ω / □, and most preferably 10Ω / □ to 100Ω / □. The surface resistance of the transparent conductive film may be 100Ω / □ or less, 60Ω / □ or less, 50Ω / □ or less, 45Ω / □ or less, or 40Ω / □. Within such a range, a particularly suitable transparent conductive film can be obtained for transparent heater applications (particularly, transparent heaters for vehicles). In one embodiment, the surface resistance of the transparent conductive film is 20Ω / □ or more. One factor for controlling the surface resistance of the transparent conductive film is the thickness of the conductive layer (the amount of fibrous conductive material in the conductive layer). By adjusting the thickness of the conductive layer so that the surface resistance is a predetermined value or more, a transparent conductive film having excellent light transmittance (for example, light transmittance in the near infrared region) can be obtained.

[0012] The transparent conductive film has a light transmittance of 85% or more, preferably 90% or more, in the wavelength region of 780 nm to 2500 nm. In this range, a transparent conductive film suitable for use in transmitting laser light in the near infrared region can be provided. For example, in the field of automatic driving of vehicles using LiDAR (Light Detection And Ranging), a transparent conductive film suitable for a member capable of efficiently transmitting laser light (near infrared region) required for sensing can be provided. A transparent conductive film having a light transmittance in the wavelength region of 780 nm to 2500 nm in the above range can be obtained, for example, by forming a conductive layer containing metal nanowires. The higher the light transmittance in the wavelength region of 780 nm to 2500 nm, the more preferable, and the upper limit is, for example, 95% (preferably 98%). In this specification, the light transmittance in a wavelength region of a certain range means the maximum light transmittance in the range. That is, “light transmittance in the wavelength region of 780 nm to 2500 nm” is synonymous with “the maximum value of light transmittance in the wavelength region of 780 nm to 2500 nm.” The light transmittance can be measured using a predetermined spectrophotometer.

[0013] In one embodiment, the transparent conductive film is used in a transparent heater (e.g., a transparent heater for a vehicle). The transparent heater may have any appropriate configuration. Typically, the transparent heater may be configured to generate heat by passing electricity through a transparent conductive film having a pair of electrodes arranged thereon. In the transparent heater, the transparent conductive film may be used as a heat source. A transparent conductive film having a conductive layer containing metal nanowires is advantageous in that it has excellent heat generation characteristics, and combined with its excellent near-infrared transmittance, it may be preferably used, for example, in an anti-fogging heater (transparent heater) for a vehicle window glass.

[0014] The transparent conductive film has a light transmittance of preferably 80% or more, more preferably 85% or more, and particularly preferably 90% or more in the wavelength region of 900 nm to 1600 nm. In such a range, the above-mentioned effect becomes remarkable. The higher the light transmittance in the wavelength region of 900 nm to 1600 nm, the more preferable, and the upper limit is, for example, 95% (preferably 98%). The "light transmittance in the wavelength region of 900 nm to 1600 nm" and the "maximum value of the light transmittance in the wavelength region of 900 nm to 1600 nm" are synonymous. In one embodiment, the transparent conductive film has a minimum light transmittance of 80% or more in the wavelength region of 900 nm to 1600 nm. That is, the light transmittance may be 80% or more in the entire wavelength region of 900 nm to 1600 nm. In the entire wavelength region of 900 nm to 1600 nm, the light transmittance is more preferably 85% or more, and even more preferably 90% or more.

[0015] The ratio (T905 / T555) of the light transmittance (T905) at a wavelength of 905 nm to the light transmittance (T555) at a wavelength of 555 nm is preferably greater than 0.95 and less than 1.2, more preferably 0.95 to 1.2, more preferably 0.98 to 1.15, even more preferably 0.99 to 1.1, even more preferably 1 to 1.1, and particularly preferably 1 to 1.05. In one embodiment, T905 / T555 is greater than 0.95 and less than 1.1. If it is within such a range, a transparent conductive film that can preferably transmit laser light required for sensing can be obtained.

[0016] The light transmittance at a wavelength of 905 nm is preferably 85% or more, more preferably 88% or more, and even more preferably 90% or more. Within such a range, a transparent conductive film suitable for use in transmitting laser light in the near infrared region can be provided. The higher the light transmittance at a wavelength of 905 nm, the more preferable it is, and the upper limit is, for example, 95% (preferably 98%).

[0017] The light transmittance at a wavelength of 555 nm is preferably 80% or more, and more preferably 85% to 95%.

[0018] The transparent conductive film has a thickness of preferably 10 μm to 500 μm, more preferably 15 μm to 300 μm, and further preferably 20 μm to 200 μm.

[0019] B. Conductive layer In one embodiment, the conductive layer includes a fiber-based conductive material and a polymer matrix. By forming a conductive layer including a fiber-based conductive material, a transparent conductive film having excellent flexibility and excellent light transmittance can be obtained. The fiber-based conductive material is protected by the polymer matrix. As a result, corrosion of the fiber-based conductive material is prevented, and a transparent conductive film having excellent durability can be obtained.

[0020] The conductive layer has a thickness of preferably 50 nm to 300 nm, and more preferably 80 nm to 200 nm.

[0021] (Conductive fiber material) As the fiber-based conductive material, metal nanowires can be preferably used.

[0022] Metal nanowires are conductive materials made of metal, shaped like needles or threads, and with a diameter of nanometers. Metal nanowires may be straight or curved. By using a conductive layer made of metal nanowires, the metal nanowires can be made into a mesh shape, so that even a small amount of metal nanowires can form a good electrical conduction path, and a transparent conductive film with low electrical resistance can be obtained. Furthermore, by making the metal nanowires into a mesh shape, openings can be formed in the gaps of the mesh, so that a transparent conductive film with high light transmittance can be obtained.

[0023] The ratio of the thickness d to the length L of the fiber-based conductive material (preferably, metal nanowires) (aspect ratio: L / d) is preferably 10 to 100,000, more preferably 50 to 100,000, and particularly preferably 100 to 10,000. If a fiber-based conductive material with such a large aspect ratio is used, the fiber-based conductive material can be well crossed, and a small amount of the fiber-based conductive material can exhibit high conductivity. As a result, a transparent conductive film with high light transmittance can be obtained. In this specification, the "thickness of the fiber-based conductive material" means the diameter when the cross section of the fiber-based conductive material is circular, means the minor axis when the cross section is elliptical, and means the longest diagonal when the cross section is polygonal. The thickness and length of the fiber-based conductive material can be confirmed by a scanning electron microscope or a transmission electron microscope.

[0024] The thickness of the fibrous conductive material (preferably metal nanowires) is preferably less than 500 nm, more preferably less than 200 nm, particularly preferably 10 nm to 100 nm, and most preferably 10 nm to 50 nm. Within such a range, a conductive layer with high light transmittance can be formed.

[0025] The length of the fibrous conductive material (preferably metal nanowires) is preferably 1 μm to 1000 μm, more preferably 10 μm to 500 μm, and particularly preferably 10 μm to 100 μm. Within such a range, a transparent conductive film with high conductivity can be obtained.

[0026] As the metal constituting the metal nanowire, any suitable metal can be used as long as it is a conductive metal. Examples of the metal constituting the metal nanowire include silver, gold, copper, nickel, and the like. Materials obtained by plating these metals (e.g., gold plating) may also be used. Among these, silver, copper, or gold are preferred from the viewpoint of conductivity, and silver is more preferred.

[0027] Any suitable method may be adopted as the method for producing the metal nanowires. For example, a method of reducing silver nitrate in a solution, a method of applying a voltage or current from the tip of a probe to the surface of a precursor, drawing out the metal nanowire at the tip of the probe, and continuously forming the metal nanowire may be mentioned. In the method of reducing silver nitrate in a solution, silver nanowires may be synthesized by liquid-phase reduction of silver salts such as silver nitrate in the presence of polyols such as ethylene glycol and polyvinylpyrrolidone. Silver nanowires of uniform size can be mass-produced according to the methods described in, for example, Xia, Y. et al., Chem. Mater. (2002), 14, 4736-4745 and Xia, Y. et al., Nano letters (2003) 3(7), 955-960.

[0028] The content of the fibrous conductive material (preferably metal nanowires) in the conductive layer is preferably 30% by weight to 90% by weight, more preferably 45% by weight to 80% by weight, based on the total weight of the conductive layer. If the content is within this range, a transparent conductive film having excellent conductivity and light transmittance can be obtained.

[0029] When the metal nanowires are silver nanowires, the density of the conductive layer is preferably 1.3 g / cm 3 ~10.5g / cm 3 and more preferably 1.5 g / cm 3 ~3.0g / cm 3 Within such a range, a transparent conductive film having excellent electrical conductivity and light transmittance can be obtained.

[0030] In one embodiment, the conductive layer is patterned. As a patterning method, any suitable method can be adopted depending on the form of the conductive layer. The shape of the pattern of the conductive layer can be any suitable shape depending on the application. For example, the patterns described in JP-T-2011-511357, JP-A-2010-164938, JP-A-2008-310550, JP-T-2003-511799, and JP-T-2010-541109 can be mentioned. After the conductive layer is formed on the substrate, it can be patterned using any suitable method depending on the form of the conductive layer.

[0031] In one embodiment, the metal nanowires in the conductive layer have a fused network structure. The metal nanowires having the fused network structure are in a state where the metal nanowires are fused to each other at their contact points. By forming a conductive layer including the metal nanowires having a fused network structure, a transparent conductive film with higher conductivity can be obtained without impairing transparency.

[0032] The conductive layer including the metal nanowires having the above-mentioned fused network structure can be formed, for example, by adding an additive for promoting fusion to the metal nanowire dispersion liquid used in forming the conductive layer. Examples of the additive include metal halides (e.g., LiCl, CsCl, NaF, NaCl, NaBr, NaI, KCl, MgCl2, CaCl2, AlCl3, AgF, etc.), inorganic acids (e.g., nitric acid, nitrous acid, sulfuric acid, etc.), organic acids (e.g., oxalic acid, citric acid, formic acid, acetic acid, lactic acid, propionic acid, butyric acid, acrylic acid, pyruvic acid, trichloroacetic acid, trifluoroacetic acid, hexanoic acid, octanoic acid, decanoic acid, dodecanoic (lauric) acid, tetradecanoic (myristic) acid, hexadecanoic (palmitic) acid, octadecanoic (stearic) acid, 2-ethylbutyric ... methylhexanoic acid, 2-ethylhexanoic acid, 2-propylpentanoic acid, pivalic acid, neoheptanoic acid, neononanoic acid, neodecanoic acid, etc.), silver salts (for example, silver nitrate, silver nitrite, silver lactate, silver chloride, silver sulfate, silver oxide, silver acetate, silver chlorate, silver sulfide, silver formate, silver hexanoate, silver octanoate, silver decanoate, silver dodecanoate, silver tetradecanoate, silver hexadecanoate, silver octadecanoate, silver pentanoate, silver pivalate, silver neoheptanoate, silver neononanoate, silver neodecanoate, etc.), compounds containing elements capable of forming silver salts (chlorine, sulfur, etc.) (hydrogen chloride, sodium chloride, etc.), etc. Among these, metal halides are preferred, and NaCl, AgF, LiF, Nabr, or NaF is more preferred. In one embodiment, the conductive layer including the metal nanowires having the fused network structure can be formed by applying the metal nanowire dispersion liquid including the additive, followed by heat treatment and / or pressure treatment. The temperature of the heat treatment is, for example, 50°C to 200°C.

[0033] The conductive layer including the metal nanowires having the fused network structure may be formed by exposing a coating layer of the metal nanowire dispersion to an acid halide vapor, such as HCl, HBr, HI, or a mixture thereof.

[0034] Metal nanowires having a fused network structure and a method for producing the same are described, for example, in JP-T-2015-530693, the disclosure of which is incorporated herein by reference.

[0035] (Polymer Matrix) Any suitable polymer may be used as the polymer constituting the polymer matrix. Examples of the polymer include acrylic polymers; polyester polymers such as polyethylene terephthalate; aromatic polymers such as polystyrene, polyvinyl toluene, polyvinyl xylene, polyimide, polyamide, and polyamideimide; polyurethane polymers; epoxy polymers; polyolefin polymers; acrylonitrile-butadiene-styrene copolymers (ABS); cellulose; silicon polymers; polyvinyl chloride; polyacetate; polynorbornene; synthetic rubber; and fluorine-based polymers. Preferably, a curable resin (preferably an ultraviolet-curable resin) composed of a polyfunctional acrylate such as pentaerythritol triacrylate (PETA), neopentyl glycol diacrylate (NPGDA), dipentaerythritol hexaacrylate (DPHA), dipentaerythritol pentaacrylate (DPPA), and trimethylolpropane triacrylate (TMPTA) is used. The polymer matrix may be a resin constituting a protective layer (details will be described later).

[0036] The polymer matrix can be formed by forming a layer of a fiber-based conductive material on a substrate, applying a polymer solution onto the layer, and then drying or curing the applied layer. This operation forms a conductive layer in which a fiber-based conductive material exists in a polymer matrix. The polymer solution contains a polymer that constitutes the polymer matrix, or a precursor of the polymer (a monomer that constitutes the polymer). The polymer solution can contain a solvent. Examples of the solvent contained in the polymer solution include alcohol-based solvents, ketone-based solvents, tetrahydrofuran, hydrocarbon-based solvents, and aromatic solvents. Preferably, the solvent is volatile. The boiling point of the solvent is preferably 200°C or less, more preferably 150°C or less, and even more preferably 100°C or less.

[0037] C. Protective layer The thickness of the protective layer is preferably from 10 nm to 1000 nm, and more preferably from 60 nm to 800 nm. Within such a range, a transparent conductive film having excellent durability can be obtained.

[0038] The total thickness of the conductive layer and the protective layer is preferably 60 nm to 1000 nm, and more preferably 70 nm to 800 nm. If it is within such a range, a transparent conductive film having excellent durability can be obtained.

[0039] Typically, the protective layer is made of a resin. Any suitable resin may be used as the resin constituting the protective layer as long as the effect of the present invention can be obtained. Examples of the resin include acrylic resins; polyester resins such as polyethylene terephthalate; aromatic resins such as polystyrene, polyvinyl toluene, polyvinyl xylene, polyimide, polyamide, and polyamideimide; polyurethane resins; epoxy resins; polyolefin resins; acrylonitrile-butadiene-styrene copolymers (ABS); cellulose; silicone resins; polyvinyl chloride; polyacetate; polynorbornene; synthetic rubber; and fluorine resins.

[0040] In one embodiment, a curable resin (e.g., an active energy ray curable resin, a thermosetting resin) is used as the resin for forming the protective layer. The protective layer made of a curable resin can be formed by curing a composition for forming a curable protective layer.

[0041] In one embodiment, the curable resin is a cured product of a composition for forming a curable protective layer containing a (meth)acrylate monomer and / or a (meth)acrylate oligomer. By using such a resin, a protective layer with a preferably adjusted shear strength can be obtained. Specific examples of the (meth)acrylate monomer and the acrylate oligomer include, for example, trimethylolpropane tri(meth)acrylate, ethylene oxide modified trimethylolpropane tri(meth)acrylate, propylene oxide modified trimethylolpropane tri(meth)acrylate, trimethylolpropane tetra(meth)acrylate, tris(acryloxyethyl)isocyanurate, caprolactone modified tris(acryloxyethyl)isocyanurate, pentaerythritol, and the like. Examples of the monomers and polymers include pentane tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, alkyl-modified dipentaerythritol tri(meth)acrylate, alkyl-modified dipentaerythritol tetra(meth)acrylate, alkyl-modified dipentaerythritol penta(meth)acrylate, and caprolactone-modified dipentaerythritol hexa(meth)acrylate. Among these, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, or dipentaerythritol penta(meth)acrylate are preferred. The above monomers and polymers may be used alone or in combination of two or more.

[0042] In one embodiment, the curable resin is a cured product of a composition for forming a curable protective layer containing a urethane (meth)acrylate oligomer. By using such a resin, a protective layer with a favorably adjusted shear strength can be obtained. Examples of the urethane (meth)acrylate oligomer include an oligomer obtained by reacting a polyol with a polyisocyanate and then reacting a (meth)acrylate having a hydroxyl group, an oligomer obtained by reacting a polyisocyanate with a (meth)acrylate having a hydroxyl group and then reacting a polyol, and an oligomer obtained by reacting a polyisocyanate, a polyol, and a (meth)acrylate having a hydroxyl group.

[0043] Examples of polyols include polyethylene glycol, polypropylene glycol, polytetramethylene ether glycol and copolymers thereof, ethylene glycol, propylene glycol, 1,4-butanediol, 2,2'-thiodiethanol, and the like.

[0044] Examples of polyisocyanates include isophorone diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, m-phenylene diisocyanate, p-phenylene diisocyanate, hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, 4,4'-diphenylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, 1,3-xylylene diisocyanate, and 1,4-xylylene diisocyanate.

[0045] Preferably, the composition for forming the curable protective layer contains any suitable photopolymerization initiator. Examples of the photopolymerization initiator include benzoin ethers such as benzoin normal butyl ether and benzoin isobutyl ether, benzil ketals such as benzil dimethyl ketal and benzil diethyl ketal, acetophenones such as 2,2-dimethoxyacetophenone and 2,2-diethoxyacetophenone, 1-hydroxycyclohexyl phenyl ketone, [2-hydroxy-2-methyl-1-(4-ethylenephenyl)propan-1-one], 2-hydroxy-2-methyl-1-phenylpropan-1-one, 1-[4-(2-hydroxyethoxy)phenyl]-2-hydroxy-2-methyl-1-propan-1-one, 2-hydroxy-2-methyl-1-(4-isopropylphenyl)propanone, and the like. Examples of the monoacylphosphine oxide include α-hydroxyalkylphenones such as Pan-1-one, α-aminoalkylphenones such as 2-methyl-1-[4-(methylthio)phenyl]-1-morpholinopropane and 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-1-butanone, monoacylphosphine oxides such as 2,4,6-trimethylbenzoyldiphenylphosphine oxide and 2,4,6-trimethylbenzoylphenylethoxyphosphine oxide, and monoacylphosphine oxides such as bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide and bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide.

[0046] D. Base material The substrate is typically made of any suitable resin. Examples of the resin constituting the substrate include cycloolefin resins, polyimide resins, polyvinylidene chloride resins, polyvinyl chloride resins, polyethylene terephthalate resins, and polyethylene naphthalate resins. Cycloolefin resins are preferably used.

[0047] The glass transition temperature of the resin constituting the above-mentioned base material is preferably 50°C to 200°C, more preferably 60°C to 180°C, and further preferably 70°C to 160°C.

[0048] The thickness of the substrate is preferably 8 μm to 500 μm, more preferably 10 μm to 250 μm, further preferably 10 μm to 150 μm, and particularly preferably 15 μm to 100 μm.

[0049] The total light transmittance of the substrate is preferably 80% or more, more preferably 85% or more, and particularly preferably 90% or more. Within such a range, a transparent conductive film suitable for use in a transparent heater or the like can be obtained.

[0050] The tensile breaking strength of the substrate at 23°C is preferably 30 MPa to 100 MPa, more preferably 50 MPa to 95 MPa, and further preferably 70 MPa to 90 MPa. According to the present invention, even if a film having poor flexibility is used, it is possible to make the transparent conductive film exhibit sufficient flexibility. The tensile breaking strength is measured at room temperature (23°C) in accordance with JIS K 7161.

[0051] The substrate may further contain any suitable additive as necessary. Specific examples of additives include plasticizers, heat stabilizers, light stabilizers, lubricants, antioxidants, UV absorbers, flame retardants, colorants, antistatic agents, compatibilizers, crosslinking agents, and thickeners. The type and amount of additives used may be appropriately set according to the purpose.

[0052] If necessary, various surface treatments may be performed on the substrate. Any suitable method may be used for the surface treatment depending on the purpose. Examples of the surface treatment include low pressure plasma treatment, ultraviolet irradiation treatment, corona treatment, flame treatment, and acid or alkali treatment. In one embodiment, the transparent substrate is surface-treated to make the transparent substrate surface hydrophilic. If the substrate is hydrophilized, the processability when applying the conductive layer-forming composition prepared from an aqueous solvent is excellent. In addition, a transparent conductive film having excellent adhesion between the substrate and the conductive layer can be obtained. In addition, the substrate may have a multi-layer structure, and may be composed of, for example, a resin film and another layer formed on the resin film.

[0053] E. Manufacturing method of transparent conductive film The transparent conductive film can be produced by any appropriate method. In one embodiment, the conductive layer-forming composition containing metal nanowires is applied to a substrate, and then a protective layer-forming composition (polymer liquid) is applied to the substrate to form the transparent conductive film. Alternatively, the protective layer-forming composition may contain metal nanowires, and the protective layer-forming composition containing the metal nanowires may be applied to the substrate to obtain a transparent conductive film.

[0054] The conductive layer forming composition may contain any suitable solvent in addition to the metal nanowires. The conductive layer forming composition may be prepared as a dispersion of the metal nanowires. Examples of the solvent include water, alcohol-based solvents, ketone-based solvents, ether-based solvents, hydrocarbon-based solvents, aromatic solvents, and the like. From the viewpoint of reducing the environmental load, it is preferable to use water. The conductive layer forming composition may further contain any suitable additive depending on the purpose. Examples of the additive include a corrosion inhibitor that prevents corrosion of the metal nanowires, a surfactant that prevents aggregation of the metal nanowires, and the like. The type, number, and amount of the additive used may be appropriately set depending on the purpose.

[0055] The dispersion concentration of the metal nanowires in the conductive layer-forming composition is preferably 0.1% by weight to 1% by weight. Within this range, a conductive layer having excellent conductivity and light transparency can be formed.

[0056] Any appropriate method may be adopted as a method for applying the conductive layer-forming composition. Examples of the application method include spray coating, bar coating, roll coating, die coating, inkjet coating, screen coating, dip coating, letterpress printing, intaglio printing, and gravure printing. Any appropriate drying method (e.g., natural drying, air drying, heat drying) may be adopted as a method for drying the coating layer. For example, in the case of heat drying, the drying temperature is typically 50°C to 200°C, and preferably 80°C to 150°C. The drying time is typically 1 minute to 10 minutes.

[0057] The protective layer forming composition includes a resin that forms a protective layer, or a precursor thereof (monomer, oligomer). The protective layer forming composition may further include any appropriate additive, if necessary. For example, a photopolymerization initiator, a coupling agent, etc. may be included. The protective layer forming composition may further include any appropriate solvent for dilution. Examples of the solvent include toluene, butyl acetate, isobutanol, ethyl acetate, cyclohexane, cyclohexanone, methylcyclohexanone, hexane, acetone, methyl ethyl ketone, methyl isobutyl ketone, propylene glycol monomethyl ether, diethyl ether, ethylene glycol, etc.

[0058] The method for applying the composition for forming a protective layer may be any appropriate method, such as spray coating, bar coating, roll coating, die coating, inkjet coating, screen coating, dip coating, letterpress printing, intaglio printing, gravure printing, or the like.

[0059] When a curable protective layer forming composition is used, the composition is applied and then cured. Any appropriate method is adopted as the curing method depending on the composition of the curable protective layer forming composition. For example, the curing method may be a method of heating and drying the solvent, followed by curing the composition with 500 mW / cm irradiator using an ultraviolet irradiator. 2 ~3000mW / cm2 At an irradiation intensity of 50 mJ / cm, the work load is 50 mJ / cm 2 ~400mJ / cm 2 One method is to irradiate the material with ultraviolet light. EXAMPLES

[0060] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. The methods for measuring the various properties are as follows. In the examples and comparative examples, "parts" and "%" are by weight unless otherwise specified. (1)Surface resistance The surface resistance of the transparent conductive film was measured using a Napson product called "EC-80." The measurement temperature was 23°C. (2) Transmittance The transmittance in the wavelength range of 780 nm to 2500 nm was measured at room temperature using the transmittance measurement mode of the "Hitachi Spectrophotometer U-4100" manufactured by Hitachi High-Tech Science Corp. Table 1 shows the transmittance at wavelengths of 555 nm and 905 nm, their ratio (T905 nm / T555 nm), and the maximum and minimum transmittance in the range of 900 nm to 1600 nm.

[0061] [Production Example 1] (Synthesis of silver nanowires and preparation of silver nanowire dispersion) In a reaction vessel equipped with a stirrer, 5 ml of anhydrous ethylene glycol and an anhydrous ethylene glycol solution of PtCl2 (concentration: 1.5 × 10 -40.5ml of AgNO3 (concentration: 0.12 mol / L) was added. After 4 minutes, 2.5ml of anhydrous ethylene glycol solution of AgNO3 (concentration: 0.12 mol / L) and 5ml of anhydrous ethylene glycol solution of polyvinylpyrrolidone (MW: 55000) (concentration: 0.36 mol / L) were simultaneously added dropwise to the resulting solution over 6 minutes. After this addition, the solution was heated to 160°C for over 1 hour to react until AgNO3 was completely reduced, producing silver nanowires. Next, acetone was added to the reaction mixture containing the silver nanowires obtained as described above until the volume of the reaction mixture was 5 times that of the reaction mixture, and the reaction mixture was centrifuged (2000 rpm, 20 minutes) to obtain silver nanowires. The obtained silver nanowires had a short diameter of 30 nm to 40 nm, a long diameter of 30 nm to 50 nm, and a length of 5 μm to 50 μm. The silver nanowires (concentration: 0.2% by weight) and pentaethylene glycol dodecyl ether (concentration: 0.1% by weight) were dispersed in pure water to prepare silver nanowire dispersion liquid I.

[0062] [Example 1] The silver nanowire dispersion I obtained in Production Example 1 was applied onto a substrate (polyethylene terephthalate film, manufactured by Mitsubishi Chemical Corporation, product name "T910E125", thickness 125 μm) using a die coater so that the resistance value after film formation would be 100 Ω / □, and the film was formed by heating at 120°C for 2 minutes. Furthermore, a monomer composition having a solid content concentration of 1% by weight obtained by diluting 1 part by weight of pentaerythritol triacrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd., product name "Viscoat #300") and 0.1 part by weight of a photopolymerization initiator (manufactured by BASF, product name "Irgacure 907") with 59 parts by weight of isopropyl alcohol and 25 parts by weight of diacetone alcohol was applied to the silver nanowire ink-coated surface using a spin coater so that the dry film thickness would be 70 nm, and the coating was heated at 80°C for 1 minute, followed by irradiation with a high-pressure mercury lamp with an integrated exposure dose of 200 mJ / cm. 2 The resultant film was irradiated with ultraviolet light of 1000 nm to obtain a transparent conductive film consisting of a substrate, a conductive layer and a protective layer.

[0063] [Example 2] A transparent conductive film was obtained in the same manner as in Example 1, except that the silver nanowire dispersion I obtained in Production Example 1 was applied onto a substrate (cycloolefin (norbornene)-based resin film (manufactured by Zeon Corporation, product name "ZEONOR ZF16", thickness 40 μm) using a die coater so that the resistance value after film formation was 37 Ω / □.

[0064] [Example 3] A transparent conductive film was obtained in the same manner as in Example 2, except that the silver nanowire dispersion I obtained in Manufacturing Example 1 was applied using a die coater so that the resistance value after film formation was 25 Ω / □.

[0065] [Example 4] A transparent conductive film was obtained in the same manner as in Example 2, except that the silver nanowire dispersion I obtained in Production Example 1 was applied using a die coater so that the resistance value after film formation was 20 Ω / □.

[0066] [Example 5] A transparent conductive film was obtained in the same manner as in Example 2, except that the silver nanowire dispersion I obtained in Manufacturing Example 1 was applied using a die coater so that the resistance value after film formation was 18 Ω / □.

[0067] [Example 6] A transparent conductive film was obtained in the same manner as in Example 2, except that the silver nanowire dispersion I obtained in Production Example 1 was applied using a die coater so that the resistance value after film formation was 13 Ω / □.

[0068] [Comparative Example 1] A sintered target containing indium oxide and tin oxide in a weight ratio of 90:10 or 96.7:3.3 was attached to a parallel plate winding magnetron sputtering device. After that, a film was formed by reactive sputtering on one side of a substrate (polyethylene terephthalate film, manufactured by Mitsubishi Chemical Corporation, product name "T910E125", thickness 125μm) in an atmosphere of 5.3×10-1 Pa consisting of 80% argon gas and 20% oxygen gas. A transparent conductive layer was formed so that the resistance value after film formation was 40Ω / □. The transparent conductive film obtained as described above had a light transmittance of less than 85% in the wavelength region of 780 nm to 2500 nm.

[0069] [Table 1]

[0070] As is clear from Table 1, the present invention can provide a transparent conductive film having excellent light transmittance in the near-infrared region. The transparent conductive films of the examples are suitable for use as members capable of efficiently transmitting laser light (near-infrared region) required for sensing in the field of autonomous driving of vehicles using LiDAR (Light Detection And Ranging), for example. [Explanation of symbols]

[0071] 10 Base material 20 Conductive layer 30 protective layer 100 Transparent conductive film

Claims

1. A transparent conductive film comprising a substrate and a conductive layer disposed on at least one side of the substrate, the surface resistance value of the transparent conductive film is 200 Ω / □ or less; The maximum light transmittance of the transparent conductive film in the wavelength region of 780 nm to 2500 nm is 85% or more. Transparent conductive film.

2. 2. The transparent conductive film according to claim 1, having a surface resistance of 100 Ω / □ or less.

3. 2. The transparent conductive film according to claim 1, wherein the ratio (T905 / T555) of the light transmittance at a wavelength of 905 nm (T905) to the light transmittance at a wavelength of 555 nm (T555) is greater than 0.95 and less than or equal to 1.

1.

4. 2. The transparent conductive film according to claim 1, wherein the maximum light transmittance in the wavelength region of 900 nm to 1600 nm is 85% or more.

5. The transparent conductive film according to claim 1 , which has a light transmittance of 85% or more at a wavelength of 905 nm.

6. The transparent conductive film of claim 1 , wherein the conductive layer comprises a fiber-based conductor and a polymer matrix.

7. The transparent conductive film according to claim 6 , wherein the fiber-based conductive material is a metal nanowire.

8. The transparent conductive film according to claim 1 , which is for use in a transparent heater.

Citation Information

Patent Citations

  • Conductive composition, transparent conductor prepared using the same, and touch panel and solar cell including the transparent conductor

    JP2013008512A

  • Transition metal chalcogenide for preparing metal nanostructures, metal nanostructures obtained thereby, electronic instrument including the same, and method for manufacturing the same

    JP2021183558A

  • Ferromagnetic metal nanowire dispersion and method for manufacturing same

    WO2015163258A1

  • Silicone-based assembly layers for flexible display applications

    WO2016196460A1

  • Transparent conductive laminate

    WO2019163791A1

Cited By

  • Transparent conductive film

    JP2025065234A